2016
DOI: 10.1002/jor.23473
|View full text |Cite
|
Sign up to set email alerts
|

Clinical safety and wear resistance of the phospholipid polymer-grafted highly cross-linked polyethylene liner

Abstract: To reduce the production of wear particles and subsequent aseptic loosening, we created a human articular cartilage-mimicked surface for a highly cross-linked polyethylene liner, whose surface grafted layer consisted of a biocompatible phospholipid polymer, poly(2-methacryloyloxyethyl phosphorylcholine). Although our previous in vitro findings showed that poly(2-methacryloyloxyethyl phosphorylcholine)-grafted particles were biologically inert and caused no subsequent bone resorptive responses, and poly(2-metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…In the first phase, the femoral head rapidly moves into the liner by a phenomenon known as “bedding-in,” which is largely attributed to permanent plastic deformation and settling of the liner in the metal shell [ 19 ]. Following previous study [ 12 ], “bedding-in,” was defined as 1 year operatively. In the second phase, the femoral head slowly moves into the liner; this movement is largely attributed to true wear (material loss in the form of particles) and is considered to define the “steady-state wear rate.” The present report uses these terms to describe the measurement results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first phase, the femoral head rapidly moves into the liner by a phenomenon known as “bedding-in,” which is largely attributed to permanent plastic deformation and settling of the liner in the metal shell [ 19 ]. Following previous study [ 12 ], “bedding-in,” was defined as 1 year operatively. In the second phase, the femoral head slowly moves into the liner; this movement is largely attributed to true wear (material loss in the form of particles) and is considered to define the “steady-state wear rate.” The present report uses these terms to describe the measurement results.…”
Section: Methodsmentioning
confidence: 99%
“…Previous hip simulator studies revealed that grafting reduced wear in HXLPE acetabular liners substantially [ 10 ]. The results of multicenter clinical trials of THA with PMPC-HXLPE acetabular liners, which begun in 2007 in Japan, reported that at 1 and 5 years postoperatively, the PMPC-HXLPE acetabular liner was an improved option for THA [ 11 , 12 ]. The clinical trials reported an improvement in the clinical scores, and no revision surgery due to PMPC-HXLPE acetabular liner degradation was required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the studied liners appeared to have serious problems of surface oxidation due to a relatively large amount of free radicals created both during manufacturing and as a consequence of MPC peeling off. A more recent follow‐up study which was co‐authored by a representative of Kyocera Medical Corp., performed on 80 patients which received such implants, reported no adverse reactions and lower wear rates when compared to not‐grafted liners, but the study did not include controls and the outstandingly low average wear rate measured (0.002 mm/year) resulted to be one order of magnitude lower than the data dispersion (0.023 mm/year), which suggests the presence of (unrealistic) negative wear rate values or a few exceptionally damaged liners which were not mentioned anywhere else in the document (Moro et al, 2017). Negative average wear rates and abnormal dispersions were indeed reported on the paper (table 6; Moro et al, 2017), rising concerns on the significance and objectivity of the study itself.…”
Section: Discussionmentioning
confidence: 99%
“…used in Japan; the hip joint is expected to last longer than conventional artificial hip joints [24].…”
Section: Antibiofouling and Antimicrobial Propertiesmentioning
confidence: 99%